Modality of fear cues affects acoustic startle potentiation but not heart-rate response in patients with dental phobia - Wannemüller, André; Sartory, Gudrun; Elsesser, Karin; Lohrmann, Thomas; Jöhren, Hans P. (Frontiers in Psychology, 2015)
The acoustic startle response (SR) has consistently been shown to be enhanced by fear-arousing cross-modal background stimuli in phobics. Intra-modal fear-potentiation of acoustic SR was rarely investigated and generated inconsistent results. The present study compared the acoustic SR to phobia-related sounds with that to phobia-related pictures in 104 dental phobic patients and 22 controls. Acoustic background stimuli were dental treatment noises and birdsong and visual stimuli were dental treatment and neutral control pictures. Background stimuli were presented for 4 s, randomly followed by the administration of the startle stimulus. In addition to SR, heart-rate (HR) was recorded throughout the trials. Irrespective of their content, background pictures elicited greater startle responses than noises in both groups with a trend for phobic participants to show startle potentiation to phobia-related pictures but not noises. Unlike controls, phobics showed HR acceleration to both dental pictures and noises. HR acceleration of the phobia group was significantly positively correlated with SR in the noise condition only. The acoustic SR to phobia-related noises is likely to be inhibited by prolonged sensorimotor gating.